Recuperação de larvas de Trichostrongylus colubriformis em diferentes estratos de Brachiaria decumbens E Panicum maximum - Da Rocha, Raquel A. [UNESP]; Bricarello, Patrizia A. [UNESP]; Da Rocha, Gilberto P. [UNESP]; Amarante, Alessandro Francisco Talamini do [UNESP] (Brazilian Coll Veterinary Parasitology, 2007)
The purpose of the experiment was to evaluate infective Trichostrongylus colubriformis larvae vertical migration in two forage grass species. Experimental modules formed by eight plots, established with Brachiaria decumbens cv. Australian and Panicum maximum cv. Aruana, were used in the study, totaling four plots for each grass species. Each plot was divided into six 30 x 30 cm subplots. Larval migration was evaluated in the four seasons of the year, in different plant strata (0-7, 7-14, 14-21, 21-28 and above 28 cm). Four feces deposits were made, one in each season of the year, in the middle of 30-cm tall forage. The feces were collected from the forage ten days after each feces deposit in the experimental subplots. Grass height was measured in each of the strata immediately before the collections. The forage of the different strata was cut from an area measuring 10-cm in radius. The feces were collected manually from the subplots. There was a grass species and grass stratum interaction in the deposit made in autumn (P < 0.05). During that season, most of the larvae were recovered from the Brachiaria grass base; meanwhile, at the forage apex, the biggest average was registered in the aruana grass. Infective larvae (U) recovery was similar among the different strata during spring. In springtime, the biggest L3 recovery occurred at the 21-28 cm stratum from both forage species. No L3 was recovered from any of the No L3 was recovered from any of the grass strata during winter and summer. Study results show that migration of T colubriformis larvae was more influenced by weather conditions Than by forage species.
Trichostrongylus colubriformis larvae recovery from different Brachiaria decumbens and Panicum maximum strata
Keywords: herbage; infective larvae; sheep; Trichostrongylus colubriformis; vertical migration